2014
DOI: 10.1155/2014/609649
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Polysaccharide Elicitors on Secondary Metabolite Production and Antioxidant Response inHypericum perforatumL. Shoot Cultures

Abstract: The effects of polysaccharide elicitors such as chitin, pectin, and dextran on the production of phenylpropanoids (phenolics and flavonoids) and naphtodianthrones (hypericin and pseudohypericin) in Hypericum perforatum shoot cultures were studied. Nonenzymatic antioxidant properties (NEAOP) and peroxidase (POD) activity were also observed in shoot extracts. The activities of phenylalanine ammonia lyase (PAL) and chalcone-flavanone isomerase (CHFI) were monitored to estimate channeling in phenylpropanoid/flavon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 79 publications
(101 reference statements)
7
16
1
Order By: Relevance
“…Among the tested polysaccharides, CHI was shown as a much more prominent elicitor of naphtodianthrone production in H. perforatum cells. On the contrary, we have previously reported that CHI did not show any stimulatory effect on naphtodianthrone accumulation in H. perforatum shoots, while PEC and DEX evoked the production of HYP and PHYP (Gadzovska Simic et al 2014). Discrepancy in these data could result, either, in a better exposition of cells into the liquid medium, or in possible difficulties of CHI as an elicitor to penetrate into shoots independently of their differentiation state.…”
Section: Phenylpropanoid and Naphtodianthrone Productions Of H Perfocontrasting
confidence: 65%
See 4 more Smart Citations
“…Among the tested polysaccharides, CHI was shown as a much more prominent elicitor of naphtodianthrone production in H. perforatum cells. On the contrary, we have previously reported that CHI did not show any stimulatory effect on naphtodianthrone accumulation in H. perforatum shoots, while PEC and DEX evoked the production of HYP and PHYP (Gadzovska Simic et al 2014). Discrepancy in these data could result, either, in a better exposition of cells into the liquid medium, or in possible difficulties of CHI as an elicitor to penetrate into shoots independently of their differentiation state.…”
Section: Phenylpropanoid and Naphtodianthrone Productions Of H Perfocontrasting
confidence: 65%
“…As far as the authors are aware, naphtodianthrone production has been intensively studied in cell, tissue and organ cultures of H. perforatum (Sirvent and Gibson 2002;Walker et al 2002;Santarem et al 2008;Gadzovska et al 2013;Tusevski et al 2014b). Among the Hypericum elicitation studies, it has been reported that polysaccharides are effective elicitors of naphtodianthrone production in shoots (Kirakosyan et al 2000;Gadzovska Simic et al 2014), seedlings (Yamaner et al 2013) and calli (Vardapetyan et al 2006). Present results revealed that all applied polysaccharides increased naphtodianthrone production in the early phase of cell growth.…”
Section: Phenylpropanoid and Naphtodianthrone Productions Of H Perfosupporting
confidence: 51%
See 3 more Smart Citations